Clinical Characteristics and Outcome Analysis for HLA Loss Patients Following Partially Mismatched Related Donor Transplantation Using HLA Chimerism for Loss of Heterozygosity Analysis by Next-Generation Sequencing. (June 2022) - Wang, Andi; Li, Wenjun; Zhao, Fei; Zheng, Zhongzheng; Yang, Ting; Wang, Sanbin; Yan, Jinsong; Lan, Jianpin; Fan, Shengjin; Zhao, Mingfeng; Shen, Jianpin; Li, Xin; et al.
Genomic loss of mismatched human leukocyte antigen (HLA loss) is one of the most vital immune escape mechanisms of leukemic cells after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, the methods currently used for HLA loss analysis have some shortcomings. Limited literature has been published, especially in lymphoid malignancies. This study aims to evaluate the incidences, risk factors of HLA loss, and clinical outcomes of HLA loss patients. In all, 160 patients undergoing partially mismatched related donor (MMRD) transplantation from 18 centers in China were selected for HLA loss analysis with the next-generation sequencing (NGS)-based method, which was validated by HLA-KMR. Variables of the prognostic risk factors for HLA loss or HLA loss–related relapse were identified with the logistic regression or the Fine and Gray regression model. An HLA loss detection system, HLA-CLN [HLA chimerism for loss of heterozygosity (LOH) analysis by NGS], was successfully developed. Forty (25.0%) patients with HLA loss were reported, including 27 with myeloid and 13 with lymphoid malignancies. Surprisingly, 6 of those 40 patients did not relapse. The 2-year cumulative incidences of HLA loss (22.7% vs 22.0%, P = 0.731) and HLA loss–related relapse (18.4% vs 20.0%, P = 0.616) were similar between patients with myeloid and lymphoid malignancies. The number of HLA mismatches (5/10 vs <5/10) was significantly associated with HLA loss in the whole cohort [odds ratio (OR): 3.15, P = 0.021] and patients with myeloid malignancies (OR: 3.94, P = 0.021). A higher refined-disease risk index (OR: 6.91, P = 0.033) and donor–recipient ABO incompatibility (OR: 4.58, P = 0.057) contributed to HLA loss in lymphoid malignancies. To sum up, HLA-CLN could overcome the limitations of HLA-KMR and achieve a better HLA coverage for more patients. The clinical characteristics and outcomes were similar in patients with HLA loss between myeloid and lymphoid malignancies. In addition, the results suggested that a patient with HLA loss might not always relapse.